Reducing attrition after downsizing: Analyzing the effects of organizational support, supervisor support, and gender on organizational commitment - Adair Erickson, Robin; Roloff, Michael E. (International journal of organizational analysis (2005), 2007)
The purpose of this research is to focus on organizational support factors that facilitate organizational commitment among downsizing survivors. High attrition by employees who "survive" layoffs is common and costly. Using a sample of 2,751 employees, a secondary analysis of employee survey data examined the effects of perceived organizational support (POS), perceived supervisor support (PSS), and gender on downsizing survivors' organizational commitment. Findings indicate that organizational commitment is positively related to both POS and PSS, with POS accounting for a greater increment of variance. When predicting organizational commitment subsequent to a downsizing, POS and PSS compensate for each other in that: POS moderates the association between PSS and organizational commitment, such that the relationship becomes stronger as the level of POS decreases; and PSS moderates the association between POS and organizational commitment, such that the relationship becomes weaker as the level of PSS increases. Gender moderates the two-way interaction between POS and PSS when predicting organizational commitment such that the interaction is stronger among men than for women.